Bobwhite Brood Ecology in Relation to Fallow Field Management Techniques and Prescribed Fire Regime - A. Vincent Carver; Loren W. Burger Jr.; Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
We used compositional analysis to rank habitats used by nesting and brood-rearing northern bobwhites (Colinus virginianus) in northern Florida. We used a residence index based on brood movement rates and turning angles to predict distribution of organisms among habitat types within brood ranges. We examined relationships among residence indices and vegetation and invertebrate characteristics of the habitat to draw inferences as to brood habitat quality. We related brood survival to vegetation, landscape structure and composition, and invertebrate characteristics within brood ranges. Finally, we reported effects of season of disking (fall vs spring) on vegetative (composition, canopy cover, density, ground cover) and invertebrate (richness and biomass) communities in fallow agricultural fields.